Increased Materialistic Trends among Youth - Masood, Afsheen; Musarrat, Rubab; Mazahir, Shama (Universitas Ahmad Dahlan, 2016)
Abstract The goal of this qualitative research is to investigate the increased sense of materialism among youth. The main research question is to identify the factors which are causing materialism among youth. The sample of this research included 25 people, age group 18-25 years obtained from students that are enrolled in universities. The interpretive phenomenological approach was taken which was based on semi-structured interviews. The findings revealed that materialistic trends are increasing among youth nowadays. Because thought patterns of youth and societal demands have changed totally. Factors that are increasing materialism include social media, brand consciousness; self-centeredness; fake personality development and desire to be socially accepted. The implications indicate that materialistic trend should stop by controlling the social media possession among youth which is the primary source of enhancing materialism among youth. Keywords: social media, parenting, brand consciousness, society, and lifestyle.